PENGARUH RASIO LIKUIDITAS, RASIO LEVERAGE, DAN RASIO AKTIVITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA (BEI) - Anggraeni, Krisna (Katalogis, 2015)
The purpose of this study was to determine the effect of liquidity, leverage and profit growth in the activity of the automotive companies in Indonesia Stock Exchange (IDX) either simultaneously or partially. This research is research that requires verification testing, to determine the effect between the variables with other variables. This research was conducted on automotive companies listing on the Indonesian Stock Exchange (BEI). The population in this study are all automotive companies listing on the Indonesian Stock Exchange (BEI) from 2009 to 2013 as many as 20 companies. Based on the characteristics of the population conformity with existing criteria, then the sample studied automotive company is as many as 10 companies. Based on the analysis by multiple linear regression equation: Y = 0,087-0,052X1 + 0,594X2 + 0,222X3 + E shows the ratio of liquidity a negative influence on earnings growth, while the leverage ratio and the ratio of positive influence activity. Test results prove the hypothesis simultaneous liquidity ratios, leverage and activity give significant effect on earnings growth, while partial liquidity did not exert significant influence, while the leverage ratio and activity give significant effect on earnings growth. The management needs to do an evaluation of the increase in current assets is too large, need to consider additional debt and the need to increase efficiency in the use of capital.